Dapur Makanan Pendamping-Air Susu Ibu (MP-ASI) di Daerah Bencana Malampah, Pasaman Barat - Amalfi, Hendra; Masnadi, Nice Rachmawati (Faculty of Medicine, Universitas Andalas, 2024)
Indonesia legislation number 24 of 2007 at 55 concerning disaster management states that children (babies and toddlers) are a vulnerable group when a disaster occurs.1 Children are a vulnerable population and have special health problems that must be considered when a disaster occurs. One of them is the very limited availability of complementary foods (MP-ASI) and this condition will worsen the nutritional status of children in disaster areas.2,3,4 The provision of food menus for toddlers in natural disaster conditions is limited because public kitchen do not prepare special menu for toddlers so that children consume food that is also consumed by adults, including instant food. The availability of MP-ASI ingredient can be achieved from public kitchens with the help and cooperation of various parties including volunteers by setting up MP-ASI kitchen so that nutritional intake for toddlers is fulfilled in disaster conditions.5 This was a activities report on establishing MP-ASI in the disaster area, Malampah, Pasaman. It has been expected to be a reference for establishing MP-ASI kitchen in disaster area, as consideration in creating operational standards for establishing MP-ASI kitchen in disaster area, and assist in managing public MP-ASI kitchen in natural disaster area.